Frontispiece: Insights on Luminescent Micro‐ and Nanospheres of Infinite Coordination Polymers. Issue 2 (12th January 2022) - Arroyos, Guilherme; da Silva, Caroline M.; Theodoroviez, Lucas B.; Campanella, Jonatas E. M.; Frem, Regina C. G.
Abstract : Infinite coordination polymers (ICPs) are compounds similar to metal‐organic frameworks (MOFs), but with distinct particle morphologies. Micro‐ or nanospheres of ICPs are the most reported, which are frequently synthesized by using rare‐earth ions. This article covers the growth mechanisms of spherical ICP particles and the main applications related to luminescent properties, including chemical sensing, light emission, bioimaging and templating. Read more in the Minireview by R. C. G. Frem, G. Arroyos et al. on page 5 ff.